A high-strength wear-resistant gypsum board and preparation method thereof

By mixing and aging materials such as building gypsum powder in specific proportions, high-strength wear-resistant gypsum board with excellent mechanical and wear resistance, the problem of insufficient strength and wear resistance of existing gypsum boards is solved. , suitable for load-bearing walls and high wear resistance, and reduces production costs and equipment dependence.

CN118930215BActive Publication Date: 2024-12-13LIANYUNGANG GANGXING BUILDING MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411433149.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-13
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The mechanical strength, moisture resistance, wear resistance and fire stability of existing gypsum boards are insufficient, resulting in limited use in load-bearing walls and wear resistance areas with high requirements, and are prone to breaking during transportation and installation, affecting construction. Safety and appearance.

Method used

High-strength wear-resistant gypsum board is made of mixed construction gypsum powder, volcanic ash, foaming agent, graphene oxide fiber, boron fiber, cellulose nanocrystals, functional copolymers, retarders and binders in specific proportions. , through the aging and forming process, products with excellent mechanical properties, moisture resistance and wear resistance are obtained.

Benefits of technology

It improves the mechanical and mechanical properties, moisture-proof properties and wear resistance of gypsum board, extends the service life, and reduces production costs and equipment dependence, making it suitable for continuous large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-strength wear-resistant gypsum board and a preparation method thereof, and relates to the technical field of building materials. The gypsum board is prepared from the following raw materials by weight: 35-45 parts of building gypsum powder, 3-8 parts of volcanic ash, 1-3 parts of foaming agent, 1-3 parts of terminal amino hyperbranched polysiloxane, 8-10 parts of graphene oxide fiber, 3-5 parts of boron fiber, 1-3 parts of coupling agent, 3-5 parts of cellulose nanocrystal, 0.8-1.5 parts of functional copolymer, 0.3-0.6 parts of (3,6-diaminoacridine-9-yl) boric acid, 1-3 parts of retarder, 0.3-0.8 parts of sodium lignin sulfonate, 0.1-0.5 parts of binder, and 10-15 parts of water. The gypsum board has good mechanical properties, good moisture resistance and wear resistance, and excellent fire resistance stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a high-strength wear-resistant gypsum board and a preparation method thereof. Background Art

[0002] Gypsum board is made of building gypsum or high-strength gypsum as the main raw materials. It has the advantages of good fire resistance, sound insulation, heat insulation, green environmental protection, high strength and easy processing. It is one of the structural panels of prefabricated buildings and has been widely used in the fields of building structure engineering and decoration.

[0003] The existing gypsum board has poor mechanical strength, which makes it impossible to be used as a load-bearing wall material. It also does not have sufficient shear force to support devices fixed to the wall (such as TVs, picture frames, fire-fighting equipment, etc.). When the device exceeds a certain weight, the screws of the fixing device will be pulled out of the wall, causing it to fall off the wall. During transportation, the existing gypsum board is easy to break, which brings inconvenience to construction. In addition, after installation, the existing gypsum board will cause serious quality problems such as the shedding and cracking of the gypsum material under the action of external forces such as vibration, impact, and extrusion, as well as in a humid environment. While the shape is damaged, it not only affects the appearance of the building, but also poses certain hidden dangers to the safety of the building decoration. On the other hand, the wear resistance of the existing gypsum board is general, and it cannot meet the use in occasions with high wear resistance requirements, which limits the further development of its application scope.

[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN104386997B discloses a high-strength gypsum board, which is composed of the following raw materials by weight: 13 parts of glass slag, 40 parts of old gypsum board powder, 5 parts of paper ash, 4 parts of fly ash, 12 parts of lightweight filler, 5 parts of titanate, 3.7 parts of retarder, and 100 parts of water. The invention uses glass slag, old gypsum board, and fly ash as raw materials. The old gypsum board can be reused, and the production is formaldehyde-free and pollution-free. At the same time, paper ash and retarder are added to the raw materials to increase the strength and consistency of gypsum, ensure the strength and hardness of the gypsum board, and have good environmental protection functions. However, its moisture resistance, fire resistance stability and wear resistance still need to be further improved.

[0005] It can be seen that it is particularly important to develop a high-strength wear-resistant gypsum board with good mechanical properties, good moisture-proof and wear-resistant properties, and excellent fire-resistant stability and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a high-strength wear-resistant gypsum board with good mechanical properties, good moisture-proof and wear-resistant properties, and excellent fire-resistant stability, and a preparation method thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is: a high-strength wear-resistant gypsum board, comprising the following raw materials in parts by weight: 35-45 parts of building gypsum powder, 3-8 parts of volcanic ash, 1-3 parts of foaming agent, 1-3 parts of terminal amino hyperbranched polysiloxane, 8-10 parts of graphene oxide fiber, 3-5 parts of boron fiber, 1-3 parts of coupling agent, 3-5 parts of cellulose nanocrystals, 0.8-1.5 parts of functional copolymer, 0.3-0.6 parts of (3,6-diaminoacridine-9-yl)boric acid parts, 1-3 parts of retarder, 0.3-0.8 parts of sodium lignin sulfonate, 0.1-0.5 parts of binder, and 10-15 parts of water; the functional copolymer includes structural units introduced by the following monomers: N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and allyl β-cyclodextrin.

[0008] Preferably, the fineness of the building gypsum powder is 100-400 mesh, and is provided by Taian Jiepu Gypsum Technology Co., Ltd.

[0009] Preferably, the fineness of the volcanic ash is 200-500 mesh.

[0010] Preferably, the foaming agent is at least one of sodium dodecyl sulfate and ammonium dodecyl sulfate.

[0011] Preferably, there is no special requirement for the source of the amino-terminated hyperbranched polysiloxane. In one embodiment of the present invention, the amino-terminated hyperbranched polysiloxane is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN110156948B.

[0012] Preferably, the graphene oxide fiber is a single-layer graphene oxide fiber with an average diameter of 3-6 μm and a length of 1-3 mm; the boron fiber has an average diameter of 3-9 μm and a length of 1-5 mm.

[0013] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.

[0014] Preferably, the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Nanosyn Technology Co., Ltd.

[0015] Preferably, the preparation method of the functional copolymer comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin, and an initiator to a high boiling point solvent, stirring and reacting at 60-70°C in an inert gas atmosphere for 3-6 hours, then precipitating in water, washing the precipitated polymer with ethanol for 3-6 times, and finally drying in a vacuum drying oven at 85-95°C to constant weight to obtain a functional copolymer.

[0016] Preferably, the mass ratio of the N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin, initiator, and high boiling point solvent is 1:(0.8-1.2):(1-2):0.5:(0.03-0.05):(10-20).

[0017] Preferably, there is no special requirement for the source of the allyl-β-cyclodextrin. In one embodiment of the present invention, the allyl-β-cyclodextrin is prepared according to the method of Example 1 in CN101717518B.

[0018] Preferably, the initiator is azobisisobutyronitrile; the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone; and the inert gas is any one of nitrogen, helium, neon, and argon.

[0019] Preferably, the retarder is one or more of sodium citrate, sodium hexametaphosphate and sodium gluconate.

[0020] Preferably, the binder is α-starch, which is provided by Jiahe Energy Saving Materials Co., Ltd.

[0021] Another object of the present invention is to provide a method for preparing the high-strength wear-resistant gypsum board, comprising the following steps: mixing the raw materials uniformly by weight to obtain a slurry; transporting the slurry to an aging warehouse for aging treatment for 8-12 hours to obtain an aged material, the aging treatment temperature is 30-40°C, and the aging humidity is 32-52%; transferring the aged material to a blank mold for extrusion molding to obtain a molded blank, and finally curing, demolding, drying and shaping the molded blank to obtain a high-strength wear-resistant gypsum board.

[0022] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0023] (1) The method for preparing the high-strength wear-resistant gypsum board disclosed in the present invention has simple process, convenient operation, low dependence on equipment, low energy consumption and capital investment, high preparation efficiency and finished product qualification rate, is suitable for continuous large-scale production, and has high promotion and application value.

[0024] (2) The high-strength wear-resistant gypsum board disclosed in the present invention comprises the following raw materials in parts by weight: 35-45 parts of building gypsum powder, 3-8 parts of volcanic ash, 1-3 parts of foaming agent, 1-3 parts of terminal amino hyperbranched polysiloxane, 8-10 parts of graphene oxide fiber, 3-5 parts of boron fiber, 1-3 parts of coupling agent, 3-5 parts of cellulose nanocrystals, 0.8-1.5 parts of functional copolymer, 0.3-0.6 parts of (3,6-diaminoacridine-9-yl) boric acid, 1-3 parts of retarder, 0.3-0.8 parts of sodium lignin sulfonate, 0.1-0.5 parts of binder, and 10-15 parts of water. Through the mutual coordination and joint action of the raw materials, the gypsum board prepared has good mechanical properties, good moisture resistance and wear resistance, and excellent fire resistance stability.

[0025] (3) The high-strength wear-resistant gypsum board disclosed in the present invention, the functional copolymer includes structural units introduced by the following monomers: N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin; the cyano group, trifluoromethylphenyl, amide group, sulfonic acid group, triazone, cyclodextrin and epoxy group introduced at the same time, under the multiple effects of electronic effect, steric effect and conjugation effect, make the adhesion between the raw materials better, the product structure more compact, thereby improving the mechanical properties, wear resistance and fire resistance stability, thereby effectively extending its service life.

[0026] (4) The high-strength wear-resistant gypsum board disclosed in the present invention, the combined addition of cellulose nanocrystals and (3,6-diaminoacridine-9-yl)boric acid can not only improve the compatibility between the raw materials, but also help to improve the mechanical properties; the amino group on the (3,6-diaminoacridine-9-yl)boric acid and the terminal amino hyperbranched polysiloxane can react with the epoxy group on the functional copolymer and the graphene oxide fiber to form an interpenetrating network structure in the internal structure of the gypsum board, effectively improving the mechanical properties, wear resistance and fire stability of the product; the hyperbranched polysiloxane structure introduced by the terminal amino hyperbranched polysiloxane can not only improve the compatibility between the raw materials, but also cooperate with the cellulose nanocrystals to improve the moisture-proof performance. DETAILED DESCRIPTION

[0027] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0028] Example 1

[0029] A high-strength wear-resistant gypsum board is made of the following raw materials in parts by weight: 35 parts of building gypsum powder, 3 parts of volcanic ash, 1 part of foaming agent, 1 part of terminal amino hyperbranched polysiloxane, 8 parts of graphene oxide fiber, 3 parts of boron fiber, 1 part of coupling agent, 3 parts of cellulose nanocrystals, 0.8 parts of functional copolymer, 0.3 parts of (3,6-diaminoacridine-9-yl)boric acid, 1 part of retarder, 0.3 parts of sodium lignin sulfonate, 0.1 parts of binder, and 10 parts of water; the functional copolymer comprises structural units introduced by the following monomers: N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and allyl β-cyclodextrin.

[0030] The fineness of the building gypsum powder is 100 mesh, provided by Tai'an Jiepu Gypsum Technology Co., Ltd.; the fineness of the volcanic ash is 200 mesh; the foaming agent is sodium dodecyl sulfate; the amino-terminated hyperbranched polysiloxane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN110156948B.

[0031] The graphene oxide fiber is a single-layer graphene oxide fiber with an average diameter of 3 μm and a length of 1 mm; the boron fiber has an average diameter of 3 μm and a length of 1 mm; the coupling agent is a silane coupling agent KH550; the cellulose nanocrystal has a length of 100 nm and a diameter of 20 nm, and is provided by Beijing Naxun Technology Co., Ltd.

[0032] The preparation method of the functional copolymer comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin and an initiator to a high boiling point solvent, stirring and reacting at 60°C for 3 hours in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with ethanol for 3 times, and finally drying in a vacuum drying oven at 85°C to constant weight to obtain the functional copolymer; the N -(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin, initiator, and high boiling point solvent are in a mass ratio of 1:0.8:1:0.5:0.03:10; the allyl β-cyclodextrin is prepared according to the method of Example 1 in CN101717518B; the initiator is azobisisobutyronitrile; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is nitrogen. Through GPC test, the M of the obtained functional copolymer is measured. n =15290g / mol,M W / M n =1.417; through elemental analysis and weight change calculation, the mass ratio of the structural units introduced by N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and allyl β-cyclodextrin in the functional copolymer is 0.99:0.78:1:0.48.

[0033] The retarder is sodium citrate; the binder is α-starch, which is provided by Jiahe Energy Saving Materials Co., Ltd.

[0034] A preparation method of the high-strength wear-resistant gypsum board comprises the following steps: uniformly mixing the raw materials by weight to obtain slurry; conveying the slurry to an aging warehouse for aging treatment for 8 hours to obtain an aged material, wherein the aging treatment temperature is 30°C and the aging humidity is 32%; transferring the aged material to a blank mold for extrusion molding to obtain a molded blank, and finally curing, demolding, drying and shaping the molded blank to obtain a high-strength wear-resistant gypsum board.

[0035] Example 2

[0036] A high-strength wear-resistant gypsum board is made of the following raw materials in parts by weight: 37 parts of building gypsum powder, 4 parts of volcanic ash, 1.5 parts of foaming agent, 1.5 parts of amino-terminated hyperbranched polysiloxane, 8.5 parts of graphene oxide fiber, 3.5 parts of boron fiber, 1.5 parts of coupling agent, 3.5 parts of cellulose nanocrystals, 1 part of functional copolymer, 0.4 parts of (3,6-diaminoacridine-9-yl) boric acid, 1.5 parts of retarder, and 1.5 parts of wood 0.4 parts of sodium sulfonate, 0.2 parts of a binder, and 12 parts of water; the functional copolymer includes structural units introduced by the following monomers: N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and allyl β-cyclodextrin.

[0037] The fineness of the building gypsum powder is 200 mesh, provided by Tai'an Jiepu Gypsum Technology Co., Ltd.; the fineness of the volcanic ash is 300 mesh; the foaming agent is ammonium dodecyl sulfate; the terminal amino hyperbranched polysiloxane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN110156948B; the graphene oxide fiber is a single-layer graphene oxide fiber with an average diameter of 4μm and a length of 1.5mm; the average diameter of the boron fiber is 4μm and the length is 2mm; the coupling agent is a silane coupling agent KH560; the length of the cellulose nanocrystal is 200nm and the diameter is 40nm, provided by Beijing Naxun Technology Co., Ltd.

[0038] The preparation method of the functional copolymer comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl beta-cyclodextrin and an initiator to a high boiling point solvent, stirring and reacting at 63°C for 4 hours in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with ethanol for 4 times, and finally drying in a vacuum drying oven at 87°C to constant weight to obtain the functional copolymer; the N-(4-cyano-3-trifluoromethylphenyl) methacrylamide The mass ratio of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin, initiator and high boiling point solvent is 1:0.9:1.3:0.5:0.035:13; the allyl β-cyclodextrin is prepared according to the method of Example 1 in CN101717518B; the initiator is azobisisobutyronitrile; the high boiling point solvent is N,N-dimethylformamide; and the inert gas is helium.

[0039] The retarder is sodium hexametaphosphate; the binder is α-starch, which is provided by Jiahe Energy Saving Materials Co., Ltd.

[0040] A preparation method of the high-strength wear-resistant gypsum board comprises the following steps: uniformly mixing the raw materials by weight to obtain slurry; conveying the slurry to an aging warehouse for aging treatment for 9 hours to obtain an aged material, wherein the aging treatment temperature is 33°C and the aging humidity is 38%; transferring the aged material to a blank mold for extrusion molding to obtain a molded blank, and finally curing, demoulding, drying and shaping the molded blank to obtain a high-strength wear-resistant gypsum board.

[0041] Example 3

[0042] A high-strength wear-resistant gypsum board comprises the following raw materials in parts by weight: 40 parts of building gypsum powder, 5 parts of volcanic ash, 2 parts of foaming agent, 2 parts of terminal amino hyperbranched polysiloxane, 9 parts of graphene oxide fiber, 4 parts of boron fiber, 2 parts of coupling agent, 4 parts of cellulose nanocrystals, 1.2 parts of functional copolymer, 0.45 parts of (3,6-diaminoacridine-9-yl)boric acid, 2 parts of retarder, 0.6 parts of sodium lignin sulfonate, 0.35 parts of binder, and 13 parts of water; the functional copolymer comprises structural units introduced by the following monomers: N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and allyl β-cyclodextrin.

[0043] The fineness of the building gypsum powder is 250 mesh, provided by Tai'an Jiepu Gypsum Technology Co., Ltd.; the fineness of the volcanic ash is 350 mesh; the foaming agent is sodium dodecyl sulfate; the terminal amino hyperbranched polysiloxane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN110156948B; the graphene oxide fiber is a single-layer graphene oxide fiber with an average diameter of 4.5 μm and a length of 2 mm; the average diameter of the boron fiber is 6 μm and the length is 3.5 mm; the coupling agent is a silane coupling agent KH570; the length of the cellulose nanocrystal is 300 nm and the diameter is 60 nm, provided by Beijing Naxun Technology Co., Ltd.

[0044] The preparation method of the functional copolymer comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin and an initiator to a high boiling point solvent, stirring and reacting at 65°C for 4.5 hours in an inert gas atmosphere, then precipitating the polymer in water, washing the precipitated polymer with ethanol for 5 times, and finally drying the polymer in a vacuum drying oven at 90°C to a constant weight to obtain the functional copolymer; the N- The mass ratio of (4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin, initiator, and high boiling point solvent is 1:1:1.5:0.5:0.04:15; the allyl β-cyclodextrin is prepared according to the method of Example 1 in CN101717518B; the initiator is azobisisobutyronitrile; the high boiling point solvent is N-methylpyrrolidone; and the inert gas is neon.

[0045] The retarder is sodium gluconate; the binder is α-starch, which is provided by Jiahe Energy Saving Materials Co., Ltd.

[0046] A preparation method of the high-strength wear-resistant gypsum board comprises the following steps: uniformly mixing the raw materials by weight to obtain slurry; conveying the slurry to an aging warehouse for aging treatment for 10 hours to obtain an aged material, wherein the aging treatment temperature is 35°C and the aging humidity is 45%; transferring the aged material to a blank mold for extrusion molding to obtain a molded blank, and finally curing, demoulding, drying and shaping the molded blank to obtain a high-strength wear-resistant gypsum board.

[0047] Example 4

[0048] A high-strength wear-resistant gypsum board is made of the following raw materials in parts by weight: 43 parts of building gypsum powder, 7 parts of volcanic ash, 2.5 parts of foaming agent, 2.5 parts of terminal amino hyperbranched polysiloxane, 9.5 parts of graphene oxide fiber, 4.5 parts of boron fiber, 2.5 parts of coupling agent, 4.5 parts of cellulose nanocrystals, 1.3 parts of functional copolymer, 0.55 parts of (3,6-diaminoacridine-9-yl) boric acid, 2.5 parts of retarder, and 1.5 parts of wood. 0.7 parts of sodium sulfonate, 0.4 parts of a binder, and 14 parts of water; the functional copolymer includes structural units introduced by the following monomers: N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and allyl β-cyclodextrin.

[0049] The fineness of the building gypsum powder is 350 mesh, which is provided by Tai'an Jiepu Gypsum Technology Co., Ltd.; the fineness of the volcanic ash is 450 mesh; the foaming agent is a mixture of sodium dodecyl sulfate and ammonium dodecyl sulfate mixed in a mass ratio of 3:5; the terminal amino hyperbranched polysiloxane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN110156948B; the graphene oxide fiber is a single-layer graphene oxide fiber with an average diameter of 5μm and a length of 2.5mm; the average diameter of the boron fiber is 8μm and the length is 4mm; the coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570 mixed in a mass ratio of 1:2:3; the cellulose nanocrystal has a length of 400nm and a diameter of 90nm, and is provided by Beijing Naxun Technology Co., Ltd.

[0050] The preparation method of the functional copolymer comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl beta-cyclodextrin and an initiator to a high boiling point solvent, stirring and reacting at 68°C in an inert gas atmosphere for 5.5 hours, then precipitating in water, washing the precipitated polymer with ethanol for 6 times, and finally drying in a vacuum drying oven at 93°C to constant weight to obtain the functional copolymer; the N-(4-cyano-3-trifluoromethylphenyl)methacrylamide The mass ratio of olefin amide, 2-acrylamido-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin, initiator and high boiling point solvent is 1:1.1:1.8:0.5:0.045:18; the allyl β-cyclodextrin is prepared according to the method of Example 1 in CN101717518B; the initiator is azobisisobutyronitrile; the high boiling point solvent is a mixture of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone in a mass ratio of 1:3:5; the inert gas is argon.

[0051] The retarder is a mixture of sodium citrate, sodium hexametaphosphate and sodium gluconate in a mass ratio of 1:2:3; the binder is α-starch, which is provided by Jiahe Energy Saving Materials Co., Ltd.

[0052] A preparation method of the high-strength wear-resistant gypsum board comprises the following steps: uniformly mixing the raw materials by weight to obtain slurry; conveying the slurry to an aging warehouse for aging treatment for 11 hours to obtain an aged material, wherein the aging treatment temperature is 38°C and the aging humidity is 50%; transferring the aged material to a blank mold for extrusion molding to obtain a molded blank, and finally curing, demolding, drying and shaping the molded blank to obtain a high-strength wear-resistant gypsum board.

[0053] Example 5

[0054] A high-strength wear-resistant gypsum board is made of the following raw materials in parts by weight: 45 parts of building gypsum powder, 8 parts of volcanic ash, 3 parts of foaming agent, 3 parts of terminal amino hyperbranched polysiloxane, 10 parts of graphene oxide fiber, 5 parts of boron fiber, 3 parts of coupling agent, 5 parts of cellulose nanocrystals, 1.5 parts of functional copolymer, 0.6 parts of (3,6-diaminoacridine-9-yl)boric acid, 3 parts of retarder, 0.8 parts of sodium lignin sulfonate, 0.5 parts of binder, and 15 parts of water; the functional copolymer comprises structural units introduced by the following monomers: N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and allyl β-cyclodextrin.

[0055] The fineness of the building gypsum powder is 400 mesh, provided by Tai'an Jiepu Gypsum Technology Co., Ltd.; the fineness of the volcanic ash is 500 mesh; the foaming agent is sodium dodecyl sulfate; the terminal amino hyperbranched polysiloxane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN110156948B; the graphene oxide fiber is a single-layer graphene oxide fiber with an average diameter of 6 μm and a length of 3 mm; the average diameter of the boron fiber is 9 μm and the length is 5 mm; the coupling agent is a silane coupling agent KH550; the length of the cellulose nanocrystal is 500 nm and the diameter is 100 nm, provided by Beijing Naxun Technology Co., Ltd.

[0056] The preparation method of the functional copolymer comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl beta-cyclodextrin and an initiator to a high boiling point solvent, stirring and reacting for 6 hours at 70°C in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with ethanol for 6 times, and finally drying in a vacuum drying oven at 95°C to constant weight to obtain the functional copolymer; the N The mass ratio of -(4-cyano-3-trifluoromethylphenyl)methacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin, initiator, and high boiling point solvent is 1:1.2:2:0.5:0.05:20; the allyl β-cyclodextrin is prepared according to the method of Example 1 in CN101717518B; the initiator is azobisisobutyronitrile; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is argon.

[0057] The retarder is sodium citrate; the binder is α-starch, which is provided by Jiahe Energy Saving Materials Co., Ltd.

[0058] A preparation method of the high-strength wear-resistant gypsum board comprises the following steps: uniformly mixing the raw materials by weight to obtain slurry; conveying the slurry to an aging warehouse for aging treatment for 12 hours to obtain an aged material, wherein the aging treatment temperature is 40°C and the aging humidity is 52%; transferring the aged material to a blank mold for extrusion molding to obtain a molded blank, and finally curing, demoulding, drying and shaping the molded blank to obtain a high-strength wear-resistant gypsum board.

[0059] Comparative Example 1

[0060] A high-strength wear-resistant gypsum board and a preparation method thereof are substantially the same as those in Example 1, except that cellulose nanocrystals and (3,6-diaminoacridine-9-yl)boric acid are not added.

[0061] Comparative Example 2

[0062] A high-strength wear-resistant gypsum board and a preparation method thereof are basically the same as those in Example 1, except that no amino-terminated hyperbranched polysiloxane and functional copolymer are added.

[0063] In order to further illustrate the beneficial technical effects of the high-strength wear-resistant gypsum board involved in each embodiment of the present invention, relevant performance tests were carried out on the high-strength wear-resistant gypsum board involved in Examples 1-5 and Comparative Examples 1-2; the test was carried out with reference to JC / T 799-2016, and the wear resistance test method was as follows: Place the products of each example that have been cured for 28 days into a wear resistance testing machine, and allow the abrasive to enter the grinding area evenly at a speed of 200g / 100r. The stainless steel disc rotates for 50r. Take out the test piece from the testing machine, and measure the chord length (L) of the groove to an accuracy of 0.5mm. Each test piece is tested at least at two orthogonal positions, and the chord length is taken as the average of the two values. The abrasive cannot be reused. The wear resistance test results are calculated with reference to the provisions of Chapter 7 of GB / T3810.6-2006. The wear resistance test results are expressed in volume (V), and the average value of the two test pieces is taken as the test result, accurate to 1mm 3 .

[0064]

[0065] As can be seen from Table 1, the high-strength wear-resistant gypsum boards involved in the embodiments of the present invention have better mechanical properties, more excellent moisture resistance, flame retardancy and wear resistance than the comparative products. The combined use of cellulose nanocrystals, (3,6-diaminoacridine-9-yl)boric acid, amino-terminated hyperbranched polysiloxane and functional copolymer is beneficial to improving the above properties.

[0066] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength wear-resistant gypsum board, characterized in that: The invention comprises the following raw materials in parts by weight: 35-45 parts of building gypsum powder, 3-8 parts of volcanic ash, 1-3 parts of foaming agent, 1-3 parts of amino-terminated hyperbranched polysiloxane, 8-10 parts of graphene oxide fiber, 3-5 parts of boron fiber, 1-3 parts of coupling agent, 3-5 parts of cellulose nanocrystal, 0.8-1.5 parts of functional copolymer, 0.3-0.6 parts of (3,6-diaminoacridine-9-yl) boric acid, 1-3 parts of retarder, lignin sulfonic acid 0.3-0.8 parts of sodium, 0.1-0.5 parts of binder, and 10-15 parts of water; the functional copolymer includes structural units introduced by the following monomers: N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and allyl β-cyclodextrin.

2. The high-strength wear-resistant gypsum board according to claim 1, characterized in that: The fineness of the building gypsum powder is 100-400 meshes; the fineness of the volcanic ash is 200-500 meshes.

3. The high-strength wear-resistant gypsum board according to claim 1, characterized in that: The foaming agent is at least one of sodium lauryl sulfate and ammonium lauryl sulfate.

4. The high-strength wear-resistant gypsum board according to claim 1, characterized in that: The graphene oxide fiber is a single-layer graphene oxide fiber with an average diameter of 3-6 μm and a length of 1-3 mm; the boron fiber has an average diameter of 3-9 μm and a length of 1-5 mm; and the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.

5. The high-strength wear-resistant gypsum board according to claim 1, characterized in that: The length of the cellulose nanocrystal is 100-500nm and the diameter is 20-100nm.

6. The high-strength wear-resistant gypsum board according to claim 1, characterized in that: The preparation method of the functional copolymer comprises the following steps: adding N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl beta-cyclodextrin and an initiator to a high boiling point solvent, stirring and reacting for 3-6 hours at 60-70° C. in an inert gas atmosphere, then precipitating the polymer in water, washing the precipitated polymer with ethanol for 3-6 times, and finally drying the polymer in a vacuum drying oven at 85-95° C. to a constant weight to obtain the functional copolymer.

7. The high-strength wear-resistant gypsum board according to claim 6, characterized in that: The mass ratio of the N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, allyl β-cyclodextrin, initiator and high boiling point solvent is 1:(0.8-1.2):(1-2):0.5:(0.03-0.05):(10-20).

8. The high-strength wear-resistant gypsum board according to claim 6, characterized in that: The initiator is azobisisobutyronitrile; the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone; and the inert gas is any one of nitrogen, helium, neon, and argon.

9. The high-strength wear-resistant gypsum board according to claim 1, characterized in that: The retarder is one or more of sodium citrate, sodium hexametaphosphate and sodium gluconate; and the binder is α-starch.

10. A method for preparing the high-strength wear-resistant gypsum board according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: uniformly mixing the raw materials by weight to obtain slurry; conveying the slurry to an aging storage for aging treatment for 8-12 hours to obtain aged material, wherein the aging treatment temperature is 30-40°C and the aging humidity is 32-52%; transferring the aged material to a blank mold for extrusion molding to obtain a molded blank, and finally curing, demoulding, drying and shaping the molded blank to obtain a high-strength wear-resistant gypsum board.

Citation Information

Patent Citations

  • Preparation method and application of block polyether-beta-CD comb type demulsifying agent

    CN101717518B

  • High Strength Gypsum Board

    CN104386997B

  • A method for preparing amino-terminated hyperbranched polysiloxane-modified waterborne polyurethane

    CN110156948B

  • Preparation method and application of block polyether-beta-CD comb type demulsifying agent

    CN101717518A

  • Wear-resistant anti-cracking environment-friendly plasterboard and preparation method thereof

    CN107032732A